Phylogenetic Underpinning of Groundwater Use by Trees. Issue 18 (10th September 2021) - Knighton, James; Fricke, Evan; Evaristo, Jaivime; de Boer, Hugo Jan; Wassen, Martin Joseph
Abstract: Root water uptake (RWU) strategies shape climate‐vegetation feedbacks and ecosystem productivity. A fundamental relationship between RWU strategies and evolutionary histories (phylogeny) of trees, however, remains poorly understood. Establishing a phylogenetic basis for tree RWU, particularly groundwater use, could improve their representation in terrestrial biosphere models (TBMs) that are crucial for understanding hydrologic and ecosystem responses to climate perturbations. We explored possible phylogenetic bases for tree RWU using two independent data sets: (a) observed root and local groundwater depths representing 502 tree species, and (b) groundwater, soil, and xylem water isotopic evidence for groundwater uptake representing 412 species. Maximum rooting depths (RDMAX ), the ratio between RDMAX and mean water table depth (WT) (RDMAX /WT), and isotopic evidence of groundwater uptake showed significant phylogenetic signals, suggesting that tree RWU strategies are more similar among closely related species. Our findings may be used to parameterize species‐level RWU in TBMs, particularly for data‐poor regions. Plain Language Summary: Transpiration dominates terrestrial evapotranspiration, strongly influencing the movement of water, carbon, nutrients, and pollutants in the landscape. Despite evidence for global variations in water uptake strategies across tree species, the models that simulate water and solute movement through soils and ecosystems mostly neglect this complexity. This is in part because we lack empirical studies to parameterize species‐level variations in rooting depth in model code. Our research demonstrates via two independent data sets (observed rooting depths and isotopic evidence of groundwater uptake) that rooting depth has greater degrees of similarity in more closely related species than for distantly related species. Overall, our study finds that phylogenetic relationships of trees could provide reasonable estimates of tree groundwater use, improving global‐scale ecosystem models in the absence of empirical studies. Key Points: We tested the hypothesis that tree groundwater uptake is related to species identity Both rooting depths and the ratio of root to water table depths were significant phylogenetic signals Isotopic evidence of groundwater uptake showed a significant binary phylogenetic signal